PENGARUH PEMBELAJARAN BERBASIS WEB TERHADAP HASIL BELAJAR MAHASISWA DENGAN PERBEDAAN SELF REGULATED LEARNING - Rhamandica, Chintia (Universitas Muhammadiyah Ponorogo, 2023)
This study focuses on examining the influence of web-based learning on learning outcomes, considering the differences in self-regulated learning, as well as the interactions among students, instructors, and content in relation to self-regulated learning within web-based education. The research design employed is a quasi-experimental study with a posttest-only control group design. The subjects of the study are second-semester chemistry students. The treatment instruments consist of teaching materials, lesson plans, worksheets, syllabi, and media such as blogs and moodle. The measurement instruments include 23 multiple-choice questions as a learning outcome test and a self-regulated learning questionnaire. Data analysis utilizes t-tests and post hoc Anova. The learning outcomes of students using blogs do not show significant differences compared to those using moodle regarding differences in self-regulated learning. Educational media contribute more significantly to the learning process in blog classes compared to students' SRL abilities, while the students' SRL abilities play a greater role in the learning process in moodle classes than the educational media